Association between fluid management and dilutional coagulopathy in severe postpartum haemorrhage: a nationwide retrospective cohort study - Ada Gillissen; Thomas van den Akker; Camila Caram-Deelder; Dacia D C A Henriquez; Kitty W M Bloemenkamp; Jos J M van Roosmalen; Jeroen Eikenboom; Johanna G van der Bom; on behalf of the TeMpOH-1 study group (BMC, 2018)
Abstract Background The view that 2 l of crystalloid and 1.5 l of colloid can be infused while awaiting compatible blood for patients with major postpartum haemorrhage is based on expert opinion documents. We describe real-world changes in levels of coagulation parameters after the administration of different volumes of clear fluids to women suffering from major postpartum haemorrhage. Methods We performed a nationwide retrospective cohort study in the Netherlands among 1038 women experiencing severe postpartum haemorrhage who had received at least four units of red cells or fresh frozen plasma or platelets in addition to red cells. The volume of clear fluids administered before the time of blood sampling was classified into three fluid administration strategies, based on the RCOG guideline: < 2 L, 2-3.5 L and > 3.5 L. Outcomes included haemoglobin, haematocrit, platelet count, fibrinogen, aPTT and PT levels. Results Haemoglobin, haematocrit, platelet count, fibrinogen and aPTT were associated with volumes of clear fluids, which was most pronounced early during the course of postpartum haemorrhage. During the earliest phases of postpartum haemorrhage median haemoglobin level was 10.1 g/dl (IQR 8.5-11.6) among the women who received < 2 L clear fluids and 8.1 g/dl (IQR 7.1-8.4) among women who received > 3.5 L of clear fluids; similarly median platelet counts were 181 × 109/litre (IQR 131-239) and 89 × 109/litre (IQR 84-135), aPTT 29 s (IQR 27-33) and 38 s (IQR 35-55) and fibrinogen 3.9 g/L (IQR 2.5-5.2) and 1.6 g/L (IQR 1.3-2.1). Conclusions In this large cohort of women with severe postpartum haemorrhage, administration of larger volumes of clear fluids was associated with more severe deterioration of coagulation parameters corresponding to dilution. Our findings provide thus far the best available evidence to support expert opinion-based guidelines recommending restrictive fluid resuscitation in women experiencing postpartum haemorrhage. Trial registration Netherlands Trial Register (NTR4079), registration date July 17, 2013.